Development of liposomal Ganoderma lucidum polysaccharide: Formulation optimization and evaluation of its immunological activity. (6th March 2015) - Liu, Zhenguang; Ma, Xia; Deng, Bihua; Huang, Yee; Bo, Ruonan; Gao, Zhenzhen; Yu, Yun; Hu, Yuanliang; Liu, Jiaguo; Wu, Yi; Wang, Deyun
Highlights: RSM was chosen as the optimal method for preparation conditions of GLPL. The GLPL particles showed nearly spherical shape with uniform size. GLPL significantly stimulated proliferation of murine splenic lymphocyte singly or synergistically with PHA and LPS. Abstract: The aim of this study was to investigate the optimizing preparation conditions of Ganoderma lucidum polysaccharide liposome (GLPL) with response surface methodology (RSM) and the immunological enhancement activity of GLPL. The immunological enhancement activity of GLPL on splenocyte proliferation was measured. The optimum formulation of GLPL, in which the ratio of soybean phospholipid to cholesterol(w/w) of 11:1, the ratio of soybean phospholipid to tween-80 (w/w) of 10.5:1 and ultrasonic time(min) of 11, had higher entrapment efﬁciency (EE) of 71.43 ± 0.49% with spherical shape and uniform sizes. In addition, GLPL could significantly promote splenocyte proliferation singly or synergistically with PHA and LPS. That indicated that the immunological enhancement of Ganoderma lucidum polysaccharide (GLP) was significantly enhanced after encapsulation with the liposome.